2003
DOI: 10.1088/0957-4484/14/10/301
|View full text |Cite
|
Sign up to set email alerts
|

Printing nanoparticles from the liquid and gas phases using nanoxerography

Abstract: This paper reports on the directed self-assembly of nanoparticles onto charged surface areas with a resolution of 200 nm from the liquid phase and 100 nm from the gas phase. The charged areas required for this type of nanoxerographic printing were fabricated using a parallel method that employs a flexible, electrically conductive, electrode to charge a thin-film electret. As electrodes, we used metal-coated polymeric stamps and 10 µm thick doped silicon wafers carrying a pattern in topography. Each electrode w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 48 publications
0
52
0
Order By: Relevance
“…Krinke et al (2001) demonstrated 100-nm patterns of gold particles deposited from a gas phase onto a silicon dioxide substrate. Barry et al (2003) developed PDMS stamps to be used as electrodes for electrifying patterns onto PMMA substrates. Recently, Naujoks and Stemmer (2004) demonstrated that a xerography-like process allows the direct fabrication of sub-micron spots of bio-molecules from an insulating oil phase .…”
Section: Magnetic Manipulationmentioning
confidence: 99%
“…Krinke et al (2001) demonstrated 100-nm patterns of gold particles deposited from a gas phase onto a silicon dioxide substrate. Barry et al (2003) developed PDMS stamps to be used as electrodes for electrifying patterns onto PMMA substrates. Recently, Naujoks and Stemmer (2004) demonstrated that a xerography-like process allows the direct fabrication of sub-micron spots of bio-molecules from an insulating oil phase .…”
Section: Magnetic Manipulationmentioning
confidence: 99%
“…A number of concepts have been developed to print nanoparticles directly from powder and solution. Sub -one micrometer resolution assembly has been accomplished using charge directed nanoxerographic printing [1,2] and topographically directed assembly incorporating both capillary and electrostatic forces [3,4]. While the solution methods have emerged, directed self-assembly processes from the gas phase are not widely available but immensely important.…”
Section: Introductionmentioning
confidence: 99%
“…The nanomaterial building blocks would not have to be transferred in solution as is currently the case. Solution concepts have their own set of problems -almost all of the reviewed receptor based assembly concepts [1,2,[5][6][7][8][9][10][11][12][13] require surface functionization to prevent agglomeration or to guide the assembly which often interferes with the electronic or optical properties. Direct integration from the gas phase would support the use of well established passivation concepts to create high quality nanomaterial building blocks that maintain the electronic and optoelectronic functionality.…”
Section: Introductionmentioning
confidence: 99%
“…22 In our own research we have developed a parallel charge patterning process enabling nanoxerographic printing. [12][13][14][15] Patterning of charge with 100-200 nm resolution and transfer of 50 nm to 20 µm sized particles including silver, gold, indium, iron oxide, graphitized carbon, iron beads, and Xerox toner from a powder, gas, and liquid phase [12][13][14][15] has been accomplished. …”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18]25,27 In recent years there has been an increased focus on the use of long range electrostatic forces to direct the assembly of nanomaterials since it can potentially be used to assemble a vast variety of materials (magnetic, nonmagnetic, insulating, semiconducting, conducting, organic, and inorganic materials) without altering the surface chemistry of the materials. [12][13][14][15][16][17][18]25,27 Electrostatic forces are sufficiently long range to attract nanomaterials from the gas and liquid phases. The other advantage is that global fields can be applied using electrical electrodes to program the assembly.…”
mentioning
confidence: 99%